2006
DOI: 10.1590/s1676-26492006000500008
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory aura in mesial temporal lobe epilepsy: semiologic characteristics, MRI findings and differential diagnosis with parietal lobe epilepsy

Abstract: INTRODUCTION: Somatosensory auras (SSAs) are more usually described in patients with parietal lobe epilepsy (PLE), producing more commonly a localized cutaneous tingling sensation, involving hands and fingers followed by tonic or clonic focal seizures. These usually originate in the contralateral hemisphere. Etiology includes dysplasias, tumours, ischemic or postencephalitic gliosis. However, other focal epilepsies, such as frontal and temporal, may also originate SSAs. Although this type of aura is reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
(26 reference statements)
1
8
0
Order By: Relevance
“…Our findings are in line with previous reports suggesting that SSA [8, 26, 27] and PLA [21, 22] do not necessarily indicate an extratemporal seizure onset or an independent extratemporal seizure focus in patients with pharmacoresistant temporal lobe-like epilepsy. Our findings would suggest that for the majority of our patients, SSA or PLA was the result of rapid spread of epileptic activity to perisylvian somatosensory structures such as the insular cortex and second somatosensory cortex (SII) [1, 2, 5, 6, 22, 26, 35–37] rather than from an extratemporal seizure focus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in line with previous reports suggesting that SSA [8, 26, 27] and PLA [21, 22] do not necessarily indicate an extratemporal seizure onset or an independent extratemporal seizure focus in patients with pharmacoresistant temporal lobe-like epilepsy. Our findings would suggest that for the majority of our patients, SSA or PLA was the result of rapid spread of epileptic activity to perisylvian somatosensory structures such as the insular cortex and second somatosensory cortex (SII) [1, 2, 5, 6, 22, 26, 35–37] rather than from an extratemporal seizure focus.…”
Section: Discussionsupporting
confidence: 93%
“…Although some studies have suggested that patients with pharmacoresistant TLE who exhibit SSA and PLA have a favorable prognosis following temporal lobe surgery [8, 21, 26, 27], others have reported a poor outcome in this patient population [2830]. The purpose of this study was to determine the prevalence and prognostic significance of SSA/PLA as a potential marker of insular epilepsy and thus a predictor of poor response to surgery in TLE patients.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies reported that any aura involved with epilepsy was developed mostly in a mesial temporal epilepsy. A study showed that majority of their patients with a mesial temporal epilepsy developed some sort of somatosensory aura mostly in the form of a tingling sensation in the upper extremities [5]. The study based on abdominal aura showed that development of an abdominal aura was more common in patients with temporal lobe epilepsies compared to those patients with an extra temporal epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…The study using MEG showed that both selective stimulation of A δ -fiber or C-fibers induced the ultra-late evoked brain potentials at posterior parietal cortex [37], which supported our findings in the sensations of pressure, heaviness, and fullness involving A δ -fiber and/or C-fibers. On the other hand, the relationship between the sensations of numbness and tingling and posterior parietal cortex also can be supported by tingling and numbness of limbs commonly found in patients with parietal lobe epilepsy [45, 46]. …”
Section: Discussionmentioning
confidence: 99%